How to approach a study in ethnopharmacology? Providing an example of the different research stages for newcomers to the field today - Fabien Schultz; Leif‐Alexander Garbe (Wiley, 2023)
Abstract Ethnopharmacology seeks to investigate humankind's use of natural materials, such as plants, fungi, microorganisms, animals, and minerals, for medicinal purposes. In this highly interdisciplinary field, which can be described as a bridge between the natural/medical and socio‐cultural sciences, pharmacological, anthropological, and socio‐cultural research methods are often applied, along with methods from other branches of science. When entering the field of ethnopharmacology as a newcomer, student, or early career researcher today, the tremendous amount of scientific publications, and even classical books from this field and related scientific disciplines, can be overwhelming. Ethnopharmacology has evolved over the past decades, and new key topics, such as the decolonization of the field, issues on intellectual property and benefit‐sharing, species conservation, the preservation of traditional knowledge, the protection of indigenous communities, science outreach, and climate change, have become important and urgent aspects of the field that must not be disregarded by today's ethnopharmacologists. One of the questions of newcomers will be, "Where to begin?" This review article offers a brief (and certainly not comprehensive) introduction to the science of ethnopharmacology, highlighting some of its past most notable achievements and future prospects. In addition, this article provides an example for newcomers to the field of how to address different stages that may be involved in conducting ethnopharmacological field and lab studies, including early‐stage drug discovery and community work. The example presented summarizes a series of studies conducted in the remote Greater Mpigi region of Uganda, located in East Africa. Stages of ethnopharmacological research described include ethnobotanical surveying and fieldwork, the pharmacological assessment of activity with diverse targets in the laboratory, and the transfer of results back to indigenous communities, that is, non‐financial benefit sharing as a potential best practice example. As a result of this research example, a total of six original research articles have been published on the medicinal application and ethnopharmacology of 16 plant species from the Ugandan study site, offering a large quantity of results. These six publications reflect the multifaceted nature of the interdisciplinary science of ethnopharmacology, which may serve as a reference point and inspiration for newcomers to design and conduct their own independent ethnopharmacological research endeavors at other study sites. Major bottlenecks and solutions are provided, and the current social media channels with educational ethnopharmacological content are briefly introduced.